Cost‐effectiveness of three internet‐based interventions for eating disorders: A randomized controlled trial. Issue 8 (23rd June 2022) - Rohrbach, Pieter J.; Dingemans, Alexandra E.; van Furth, Eric F.; Spinhoven, Philip; van Ginkel, Joost R.; Bauer, Stephanie; van den Akker‐Van Marle, M. Elske
Abstract: Objective: The primary aim was assessing the cost‐effectiveness of an internet‐based self‐help program, expert‐patient support, and the combination of both compared to a care‐as‐usual condition. Method: An economic evaluation from a societal perspective was conducted alongside a randomized controlled trial. Participants aged 16 or older with at least mild eating disorder symptoms were randomly assigned to four conditions: (1) Featback, an online unguided self‐help program, (2) chat or e‐mail support from a recovered expert patient, (3) Featback with expert‐patient support, and (4) care‐as‐usual. After a baseline assessment and intervention period of 8 weeks, five online assessments were conducted over 12 months of follow‐up. The main result constituted cost‐utility acceptability curves with quality‐of‐life adjusted life years (QALYs) and societal costs over the entire study duration. Results: No significant differences between the conditions were found regarding QALYs, health care costs and societal costs. Nonsignificant differences in QALYs were in favor of the Featback conditions and the lowest societal costs per participant were observed in the Featback only condition (€16, 741) while the highest costs were seen in the care‐as‐usual condition (€28, 479). The Featback only condition had the highest probability of being efficient compared to the alternatives for all acceptable willingness‐to‐pay values. Discussion: Featback, an internet‐based unguided self‐help intervention, was likely to be efficient compared to Featback with guidance from an expert patient, guidance alone and a care‐as‐usual condition. Results suggest that scalable interventions such as Featback may reduce health care costs and help individuals with eating disorders that are currently not reached by other forms of treatment. Public significance statement: Internet‐based interventions for eating disorders might reach individuals in society who currently do not receive appropriate treatment at low costs. Featback, an online automated self‐help program for eating disorders, was found to improve quality of life slightly while reducing costs for society, compared to a do‐nothing approach. Consequently, implementing internet‐based interventions such as Featback likely benefits both individuals suffering from an eating disorder and society as a whole.